ELEMENTAL ANALYSIS OF ALMONDS AND CASHEWS USING LASER-INDUCED BREAKDOWN SPECTROSCOPY (LIBS) TECHNIQUE: ANALISIS KANDUNGAN UNSUR KACANG ALMOND DAN METE MENGGUNAKAN TEKNIK LASER- INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Maria Belendina Simatupang; Mangasi Alion Marpaung (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Almonds and cashews play an important role in human health and various food products. This study aims to analyze the elemental composition of almonds and cashews using Laser-Induced Breakdown Spectroscopy (LIBS) techniques. LIBS is used to emit high-energy lasers onto samples, producing plasma that contains excited atoms. These excited atoms then emit electromagnetic radiation with characteristic wavelengths, which can be used to identify and measure the concentration of elements in the samples. The research results show that LIBS techniques can be used to accurately analyze the elemental composition of almonds and cashews. The main elements identified in almonds are magnesium (Mg), calcium (Ca), potassium (K), and phosphorus (P). The main elements identified in cashews are calcium (Ca), potassium (K), and fluorine (F).